2013
DOI: 10.1002/oby.20306
|View full text |Cite
|
Sign up to set email alerts
|

Cats differ from other species in their cytokine and antioxidant enzyme response when developing obesity

Abstract: Objectives: Obese cats show many similarities to obese people, including insulin resistance and an increased diabetes risk. However, atherosclerosis and cardiovascular disease are not seen in cats. In people, they are associated with the development of an inflammatory response, which, we hypothesized, does not occur in cats. Design and Methods: Twenty neutered cats of equal gender distribution were allowed to gain weight by offering food ad libitum and were examined before and at 10, 30, 60, and 100% weight ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
3

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 42 publications
2
42
3
Order By: Relevance
“…In a longitudinal study of feline weight gain, although energy expenditure (measured as heat production during indirect calorimetry) increased with increasing body mass, the increase tapered off as the cats approached 100% gain over their lean body weight. 23 A previous study had also shown decreased energy expenditure per metabolic body size in obese compared with lean cats, 61 although the appropriate method of normalizing energy expenditure in animals with different body composition remains a matter of debate. 62,63 Additionally, a decreased caloric requirement for weight maintenance has been shown after weight loss programs in cats and dogs, suggesting an increase in metabolic efficiency that must be surmounted during the weight maintenance period.…”
Section: Changes In Energy Regulation In Obesitymentioning
confidence: 96%
See 3 more Smart Citations
“…In a longitudinal study of feline weight gain, although energy expenditure (measured as heat production during indirect calorimetry) increased with increasing body mass, the increase tapered off as the cats approached 100% gain over their lean body weight. 23 A previous study had also shown decreased energy expenditure per metabolic body size in obese compared with lean cats, 61 although the appropriate method of normalizing energy expenditure in animals with different body composition remains a matter of debate. 62,63 Additionally, a decreased caloric requirement for weight maintenance has been shown after weight loss programs in cats and dogs, suggesting an increase in metabolic efficiency that must be surmounted during the weight maintenance period.…”
Section: Changes In Energy Regulation In Obesitymentioning
confidence: 96%
“…Additionally, there was a statistically significant increase in glucose area under the curve at 60% weight gain or greater. 23 In an earlier study, expression of the insulin-dependent glucose transporter GLUT-4 in both muscle and fat was found to be lower in obese than in lean cats, 24 suggesting a possible mechanism for decreased glucose uptake.…”
Section: Box 1 Adipose Tissue Dysfunction In Obesitymentioning
confidence: 97%
See 2 more Smart Citations
“…However, the role of inflammation in the development of obesity-induced insulin resistance has been discussed controversially in cats. Some studies, in fact, reported no changes in anti-oxidant enzymes' activity or inflammatory cytokines in obese cats (Hoenig et al, 2013;Jaso-Friedmann et al, 2008). Moreover, assays for the quantification of feline circulating cytokines and chemokines are currently not available or have not been validated appropriately.…”
Section: Dogs and Catsmentioning
confidence: 99%